Religious Pluralism and Social Boundaries: A Qualitative Study of Sunni-Alevi Interaction in Eastern Anatolia's Bayburt Province - Erbay Adem; Kalkan Rifat; Ozpolat Dogukan (Tunas Harapan Ummat Foundation, 2025)
Alevism is often perceived as a homogeneous belief system; however, research reveals significant internal diversity shaped by its dispersion across various regions and cities. Understanding the cultural and religious expressions of Alevis in different local contexts is essential to grasp the authenticity and lived experience of the faith. Despite the predominance of the Sunni-Hanafi population in Bayburt, a small Alevi community exists within the province. To date, this community has received little to no scholarly attention. This study aims to explore the cultural and social connections of Alevis residing in eight villages within Bayburt Province to the broader Alevi faith. It also examines their interactions with the surrounding Sunni population and investigates the challenges associated with the intergenerational transmission of their religious and cultural heritage. Employing a qualitative research design, data were collected through in-depth interviews conducted during field visits to these villages. The interviews provided insights into how Alevi individuals perceive their identity, construct their social world, and assign meaning to their religious practices. Findings indicate that Alevism in Bayburt is increasingly limited to symbolic practices performed at visitation centers, is largely disconnected from its ritual and ethical dimensions, and is facing serious challenges in terms of cultural continuity. The study concludes that Alevism in this region is at risk of cultural erosion and potential extinction if these patterns persist.